Estudo de adsorção de lipase de Candida rugosa em palha de milho e óxido de nióbio para aplicação em reação de hidrólise - Ferreira, Renata Deda Mendonça (2019)
As the technology advances, it has become increasingly possible to modify processes, considering the coexistence of the three pillars of sustainability: environment, economy and society; and the increase in the enzymatic consumer market is a reflection of this change. Enzymes are proteins capable of catalyzing various reactions in a specific way, reducing the production of by-products and, consequently, the need to apply treatments at the end of the reactions. Among enzymes, lipases are important in hydrolysis of triglycerides, being able to participate in synthesis reaction of a variety of compounds, including biodiesel. However, enzymes are still high-cost products, which open the door to research in the direction of finding solutions that make them more economically attractive. Immobilization appears as a cost reduction proposal, as it confers greater resistance to the enzyme without causing it to lose its catalytic activity.This work aims to study the immobilization of Candida rugosa lipase by adsorption onto niobium oxide and corn straw by conducting an initial characterization of the matrices through analyzes such as BET, MEV, ATG, XRD, IVTF and PCZ, followed by a DCCR statistical planning to evaluate the influence of the variables pH, agitation and enzyme/support ratio through the measurement of protein recovery. At the best condition, the adsorption study was carried out through kinetics, chemical equilibrium and thermodynamic adsorption, followed by the evaluation of the immobilized derivatives in terms of the influence of temperature, pH, and substrate concentration on residual activity, as well as thermal and storage stability. A 2³ with 6 axial points and 4 center point design was used for statistical analysis, varying pH 4, 5, 6, 7 and 8, agitation of 100, 125, 150, 175 and 200 rpm, and enzyme/support ratio of 8000, 10000, 12000, 14000 and 16000 U∙gsupport-1. The best condition for the corn straw was pH 4, agitation 150 rpm and enzyme/support ratio 12000 U∙gsupport-1, and for niobium oxide, the best result was for Nb600, pH 6, agitation 150 rpm, and enzyme/support ratio 8000 U∙gsupport-1. The kinetic study for corn straw resulted in a better fit for pseudo second order kinetics, while for Nb600 the best fit was for pseudo first order kinetics. For both immobilized derivatives, the Langmuir isotherm was the one that best fit the data. Adsorption thermodynamics showed that for both immobilized derivatives the adsorption was favorable, and the adsorption in corn straw approached to chemical adsorption, and the adsorption in Nb600 approached the physical adsorption. The immobilization increased the optimum temperature of both derivatives from 40 to 50 and 45 °C for DIPM and DINb600, respectively; reduced the optimum pH from 7.5 to 6.5; altered the activation energy only for Nb600; and decreased the affinity of the biocatalyst for the substrate, presenting kM equal to 241.1 μmolmL-1 for free enzyme, 309.8 μmolmL-1 for DIPM, and 300.9 μmolmL-1 for DINb600. Both immobilized derivatives demonstrated good thermal stability, preserving more than 50 % of their residual activity after 60 minutes of incubation at 60 °C for DIPM and 50 °C for DINb600. Regarding storage stability, there was approximately 12 % loss of activity for DIPM after 60 days of storage at 4 °C and 45 % for DINb600 under the same conditions.